The phantom of the Open [videorecording (DVD)] - Farnaby, Simon; Rylance, Mark; Hawkins, Sally, 1976-; Jones, Mark Lewis; Lees, Christian, 1995-; Lees, Jonah, 1995-; Davies, Jake, 1993-; Myers, Johann; Ifans, Rhys, 1967-; Waller-Bridge, Isobel, 1984-; Fraser, Kit (Cinematographer); Murray, Scott (Sony Pictures Home Entertainment, 2022)
Maurice Flitcroft, a dreamer and unrelenting optimist, managed to gain entry to The British Open Golf Championship Qualifying in 1976 and subsequently shot the worst round in Open history, becoming a folk hero in the process.